Komparasi Kinerja AC Kendaraan dengan Menggunakan Refrigeran R-134a dan R-290 - Hindratmo, Dimas Bayu; Condro Purnomo, Bagiyo; Satrio Wicaksono, Akbar; Habibi, Ilham (Borobudur Engineering Review, 2023)
The development of vapor compression refrigeration systems currently depends on the issue of environmental problems related to ozone layer depletion (ODP) and global warming potential (GWP). In addition to environmental issues, low energy use is also in the spotlight of researchers. To solve the problem of refrigeration development, natural refrigeration, especially hydrocarbons, is the focus of attention. Hydrocarbons are refrigerants that have excellent properties to be natural refrigerants. This study aims to compare the performance of refrigerant R-134a with R-290. The research used a standard vapor compression refrigeration system with a TEV-type expansion valve. The system performance is seen through compression, refrigeration effect, and COP with variations in compressor rotational speed of 1000 rpm, 1500 rpm, and 2000 rpm. The results showed that the compression work, refrigeration effect, and coefficient of performance (COP) of R-290 had a more excellent value. R-290 produces the highest compression work at a 2000 rpm compressor speed of 33.34 kJ/kg for the refrigeration effect at 1000 rpm of 353.33 kJ/kg and COP at 1500 rpm 12.32.